2021
DOI: 10.3389/fmicb.2021.664061
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomics Reveals the Anaerobic Lifestyle of Meat-Spoiling Pseudomonas Species

Abstract: The ability of certain Pseudomonas (P.) species to grow or persist in anoxic habitats by either denitrification, acetate fermentation, or arginine fermentation has been described in several studies as a special property. Previously, we had isolated strains belonging to the species P. lundensis, P. weihenstephanensis, and P. fragi from anoxic modified atmosphere packaged (MAP) minced beef and further proved their anaerobic growth in vitro on agar plates. This follow-up study investigated the anaerobic growth of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…It is clear that pseudomonads are more complex and adaptable than they are given credit; generalizations of behavior at the genus level have led to a misunderstanding regarding the environments in which they can flourish. This large genus does contain obligate aerobes but also contains obligate respirators or anoxic persisters that can grow without the presence of oxygen, utilizing additional fermentative pathways (Kolbeck et al, 2021). It has even been observed that Pseudomonas fragi strains in vacuum-packaged beef utilize more protolytic behavior and less aerobic respiration behaviors than counterparts stored aerobically (De Filippis et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that pseudomonads are more complex and adaptable than they are given credit; generalizations of behavior at the genus level have led to a misunderstanding regarding the environments in which they can flourish. This large genus does contain obligate aerobes but also contains obligate respirators or anoxic persisters that can grow without the presence of oxygen, utilizing additional fermentative pathways (Kolbeck et al, 2021). It has even been observed that Pseudomonas fragi strains in vacuum-packaged beef utilize more protolytic behavior and less aerobic respiration behaviors than counterparts stored aerobically (De Filippis et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Proteiniclasticum, Luteimonas, and Proteiniphilum are known to degrade and live on proteins using an inventory of proteases, peptidases and amino acid deaminases [44][45][46] (Additional file 2: Table S7-8). Similarly, Pseudomonas, Hydrogenophaga, Flavobacterium, and those from the Rhodobacteraceae family could obtain ammonia nitrogen from urea [47][48][49][50] (Additional file 2: Tables S6 and S7). As the pH for both storages ranged from 6.92 to 7.85 (Additional file 2: Table S2) and the pKa of ammonia is 9.2, not more than 4% of this compound will occur in the deprotonated or NH 3 form which could be released to the atmosphere (Additional file 2: Table S2).…”
Section: Characterization Of Nitrogen-transforming Microorganisms In ...mentioning
confidence: 99%
“…isolated from vacuum packaged meat are able to grow under strictly anaerobic conditions and that arginine fermentation is the primary pathway anaerobic spoilage Pseudomonas spp. use for growth (Hilgarth et al., 2019; Kolbeck et al., 2021). Although the metabolic reasons for this phenomenon require further investigation, advances in microbial sampling techniques and proteomic analysis have generated data that rebut the traditional understanding of the role of Pseudomonas spp.…”
Section: Introductionmentioning
confidence: 99%